2019
DOI: 10.1590/1980-5373-mr-2017-0203
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical and Electrochemical Evaluation of Dissimilar low Ni SS and 304 SS using Different Filler Materials

Abstract: This study investigates the effect of dissimilar metal welding of low nickel stainless steel (SS) and 304 SS employing tungsten inert gas (TIG) welding process by using three different filler materials (316L, 308L and 310 SS). Microstructural, mechanical properties and corrosion behavior in 3.5% NaCl solution was studied. The microstructural investigation revealed the formation of δ-ferrite and γ-austenite in the weld (welded by 316L and 308L filler). The Higher δ-ferrite content was found more in 316L weld zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In contrast, no precipitates are observed in the weld metal. The microstructure of the weld metal has dendritic morphology and is formed by austenite with delta ferrite formations, which corresponds with study [ 32 ], see Figure 12 b. The HAZ microstructure is formed by austenite with a rare occurrence of globular precipitates.…”
Section: Resultssupporting
confidence: 84%
“…In contrast, no precipitates are observed in the weld metal. The microstructure of the weld metal has dendritic morphology and is formed by austenite with delta ferrite formations, which corresponds with study [ 32 ], see Figure 12 b. The HAZ microstructure is formed by austenite with a rare occurrence of globular precipitates.…”
Section: Resultssupporting
confidence: 84%
“…It was observed that rapid solidification generates higher microhardness values. This is consistent with several literature data 23,24 in which the microhardness of 316L steel processed by rapid solidification is usually more significant than in the cold rolled condition.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, the heat input was computed using Equation (2) [ 18 ]. where , and are the current (in amperes), voltage (in volts), and welding speed (in mm/s), respectively.…”
Section: Methodsmentioning
confidence: 99%